2015
DOI: 10.9734/acsj/2015/16257
|View full text |Cite
|
Sign up to set email alerts
|

MHD Mixed Convection Flow Past a Vertical Porous Plate in a Porous Medium with Heat Source/Sink and Soret Effects

Abstract: The present analysis is to study the boundary layer flow of an incompressible, steady combined free-forced convection and mass transfer flow over a vertical porous plate embedded in a porous medium with the effects of heat source/sink, suction/injection and thermal diffusion under the influence of magnetohydrodynamics. The uniform magnetic field is applied along the plate. With the help of similarity transformations the partial differential equations are transformed into a coupled non-linear ordinary different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Their findings showed that, an increase of magnetic field decreases the velocity distribution. Kalyani et al (2015) studied MHD mixed convection flow past a vertical porous plate in a porous medium with heat source/sink and soret effects. Their results showed that, the effect of magnetic field is to reduce the velocity profile.…”
Section: Introductionmentioning
confidence: 99%
“…Their findings showed that, an increase of magnetic field decreases the velocity distribution. Kalyani et al (2015) studied MHD mixed convection flow past a vertical porous plate in a porous medium with heat source/sink and soret effects. Their results showed that, the effect of magnetic field is to reduce the velocity profile.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid nanofluid had been explored as a new class of nanofluid it is marked by Subhani and Nadeem [32]. Kalyani et al [18], and Sundarnath and Muthucumarswamy [33] investigated and analyzed the diffusion and ramped temperature influences through porous medium of MHD fluid flows. Fluids having microstructure are known as micropolar fluids.…”
Section: Introductionmentioning
confidence: 99%
“…) and for medium molecular weight ( ), Soret effect is found to be of considerable magnitude such that it cannot be ignored. In view of these above-mentioned studies, the many researchers [15][16][17][18][19][20][21][22][23][24][25][26] have analyzed theoretically the Soret and Dufour effects in porous medium on heat-mass transfer for convective flow and they presented their numerical solutions with various effects of heat source / sink and suction / injection.…”
Section: Introductionmentioning
confidence: 99%